Dutch workers’ attitudes towards having a coworker with mental health issues or illness: a latent class analysis - van Beukering, I. E.; Sampogna, G.; Bakker, M.; Joosen, M. C. W.; Dewa, C. S.; van Weeghel, J.; Henderson, C.; Brouwers, E. P. M. (Frontiers in Psychiatry, 2023)
Introduction Workplace mental health stigma is a major problem as it can lead to adverse occupational outcomes and reduced well-being. Although workplace climate is largely determined by managers and co-workers, the role of co-workers in workplace stigma is understudied. Therefore, the aims are: (1) to examine knowledge and attitudes towards having a coworker with Mental Health Issues or Illness (MHI), especially concerning the desire for social distance, (2) to identify distinct subgroups of workers based on their potential concerns towards having a coworker with MHI, and (3) to characterize these subgroups in terms of knowledge, attitudes, and background characteristics. Materials and methods A cross-sectional survey was conducted among a nationally representative internet panel of 1,224 Dutch workers who had paid jobs and did not hold management positions. Descriptive statistics and a three-step approach Latent Class Analysis (LCA) were used to address the research aims. Results Concerning the desire for social distance, 41.9% of Dutch workers indicated they did not want to have a close colleague with MHI, and 64.1% did not want to work for a higher-ranking manager who had MHI. In contrast however, most workers did not have negative experiences with interacting with coworkers with MHI (92.6%). Next, five distinct subgroups (SG) of workers were identified: two subgroups with few concerns towards having a coworker with MHI (SG1 and SG2; 51.8% of the respondents), one subgroup with average concerns (SG3; 22.7% of the respondents), and two subgroups with more concerns (SG4 and SG5; 25.6% of the respondents). Four out of five subgroups showed a high tendency towards the desire for social distance. Nevertheless, even in the subgroups with more concerns, (almost) half of the respondents were willing to learn more about how to best deal with coworkers with MHI. No significant differences were found between the subgroups on background characteristics. Discussion The high tendency to the desire for social distance seems to contrast with the low number of respondents who personally had negative experiences with workers with MHI in the workplace. This suggests that the tendency to socially exclude this group was not based on their own experience. The finding that a large group of respondents indicated to want to learn more about how to deal with a co-worker with MHI is promising. Destigmatizing interventions in the workplace are needed in order to create more inclusive workplaces to improve sustained employment of people with MHI. These interventions should focus on increasing the knowledge of workers about how to best communicate and deal with coworkers with MHI, they do not need to differentiate in background variables of workers.